Physical Activity in Renal Disease and the Effect on Hypertension: A Randomized Controlled Trial - Stephanie Thompson; Natasha Wiebe; Michael K. Stickland; Gabor T. Gyenes; Rachelle Davies; Jeff Vallance; Michelle Graham (Kidney & Blood Pressure Research, 2022)
Introduction: Exercise is an effective strategy for blood pressure (BP) reduction in the general population, but its efficacy for the management of hypertension in chronic kidney disease (CKD) is not known. We evaluated the difference in 24-h ambulatory systolic BP (SBP) with exercise training in people with moderate to severe CKD. Methods: Participants with an estimated glomerular filtration rate (eGFR) of 15–44 mL/min per 1.73 m2 and SBP >120 mm Hg were randomized to receive thrice-weekly moderate-intensity aerobic-based exercise over 24 weeks, or usual care. Phase 1 included supervised in-center and home-based sessions for 8 weeks. Phase 2 was 16 weeks of home-based sessions. BP, arterial stiffness, cardiorespiratory fitness, and markers of cardiovascular (CV) risk were analyzed using mixed linear regression. Results: We randomized 44 people; 36% were female, the median age was 69 years, 55% had diabetes, and the median eGFR was 28 mL/min per 1.73 m2. Compared with usual care, there was no significant change in 24-ambulatory SBP at 8 weeks (2.96 mm Hg; 95% confidence interval (CI): −2.56, 8.49) or 24 weeks. Peak oxygen uptake improved by 1.9 mL/kg/min in the exercise group (95% CI: 0.03, 3.79) at 8 weeks with a trend toward higher body mass index 1.84 kg/m2 (95% CI: −0.10, 3.78) and fat free mass, but this was not sustained at 24 weeks. Markers of CV risk were unchanged. Conclusions: Despite an improvement in peak aerobic capacity and body composition, we did not detect a change in 24-h ambulatory SBP in people with moderate-to-severe CKD.